2022
DOI: 10.3390/plants12010122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Use of Organic Fertilizer with Different Dosages on Soil Improvement, Nitrogen Transformation, Tea Yield and Quality in Acidified Tea Plantations

Abstract: In this study, sheep manure fertilizers with different dosages were used for five consecutive years to treat acidified tea plantation soils, and the effects of sheep manure fertilizer on soil pH value, nitrogen transformation, and tea yield and quality were analyzed. The results showed that soil pH value showed an increasing trend after a continuous use of sheep manure fertilizer from 2018 to 2022. After the use of low dosage of sheep manure fertilizer (6 t/hm2–15 t/hm2), tea yield, the content of tea quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…Taking this into account, the annual N fertilizer application rate in this experiment was determined to be the average value of 150 kg•hm −2 applied by local farmers as a reflection of the actual production situation in the region. Furthermore, this study did not observe a significant impact on the current year's tea leaf yield (Figure 1) as a result of organic fertilizer substitution, despite several previous studies demonstrating a positive association between organic fertilizer substitution and tea leaf yield [28,34,35].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Taking this into account, the annual N fertilizer application rate in this experiment was determined to be the average value of 150 kg•hm −2 applied by local farmers as a reflection of the actual production situation in the region. Furthermore, this study did not observe a significant impact on the current year's tea leaf yield (Figure 1) as a result of organic fertilizer substitution, despite several previous studies demonstrating a positive association between organic fertilizer substitution and tea leaf yield [28,34,35].…”
Section: Discussioncontrasting
confidence: 95%
“…The period of this experiment was only one year, which may be one of the reasons for the results acquired, but a deeper look into the pathways of the effects of organic fertilizer on tea yield shows that these effects occur mainly due to the positive effects of organic fertilizer on soil pH and ammonium-N content [3,7]. Previous studies have found that proper application of organic fertilizer can improve soil acidification [35] and change the mineral N status of soils under acidifying conditions, at which point the soils are normally dominated by nitrate N [28,36]. Although the tea plantation where this experiment was conducted had been cultivated for a long time, the soil pH was still maintained above 4.5, which is a suitable soil pH condition for tea tree growth (the optimum soil pH for tea tree growth is between 4.0 and 5.5) [12,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In response to different types of abiotic stresses, plants need synthesize different types of hormones for self-regulation to adapt to their environment and thus safeguard their growth ( Waadt et al., 2022 ). Acidification is also an abiotic stress on the tea tree itself, leading to reduced tea yield and quality ( Ye et al., 2023a ). In this study, we found that a total of 59 hormones were detected in tea tree leaves from soils with different pH values, and the hormone content showed a significant increase with the increase of soil pH, which was manifested by the total hormone content of 5.99 mg/g, 11.49 mg/g, and 15.41 mg/g when soil pH values were 3.29, 4.74, and 5.32, respectively ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Soil nitrogen transformation and its content were closely related to the number and intensity of related microorganisms and ammonifying bacteria facilitated the transformation of soil organic and mineralized nitrogen into ammonium nitrogen (Bojarszczuk et al, 2019;Yan et al, 2020a), while nitrifying bacteria converted soil ammonium nitrogen into nitrate nitrogen (Wang et al, 2022b;Yu et al, 2022). It can be seen that the application of organic fertilizer could improve soil pH value, improve soil quality, promote microbial propagation related to ammonium nitrogen transformation, increase soil ammonium nitrogen content, and thus improve crop yield and quality (Ye et al, 2022;Ye et al, 2023).…”
Section: Introductionmentioning
confidence: 99%